Nonlinear Fokker-Planck flows and their probabilistic counterparts - Barbu, Viorel 1941-; Röckner, Michael 1956- (Lecture notes in mathematics, 2024)
Introduction -- Existence of nonlinear Fokker-Planck flows -- Time dependent Fokker-Planck equations -- Convergence to equilibrium of nonlinear Fokker-Planck flows -- Markov processes associated with nonlinear Fokker-Planck equations -- Appendix